Serum cholesterol levels, HMG-CoA reductase inhibitors and the risk of intracerebral haemorrhage. The Multicenter Study on Cerebral Haemorrhage in Italy (MUCH-Italy). Issue 9 (21st March 2016) - Pezzini, Alessandro; Grassi, Mario; Iacoviello, Licia; Zedde, Marialuisa; Marcheselli, Simona; Silvestrelli, Giorgio; DeLodovici, Maria Luisa; Sessa, Maria; Zini, Andrea; Paciaroni, Maurizio; Azzini, Cristiano; Gamba, Massimo; et al.
Abstract : Objective: Although a concern exists that 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) might increase the risk of intracerebral haemorrhage (ICH), the contribution of these agents to the relationship between serum cholesterol and disease occurrence has been poorly investigated. Methods: We compared consecutive patients having ICH with age and sex-matched stroke-free control subjects in a case–control analysis, as part of the Multicenter Study on Cerebral Haemorrhage in Italy (MUCH-Italy), and tested the presence of interaction effects between total serum cholesterol levels and statins on the risk of ICH. Results: A total of 3492 cases (mean age, 73.0±12.7 years; males, 56.6%) and 3492 control subjects were enrolled. Increasing total serum cholesterol levels were confirmed to be inversely associated with ICH. We observed a statistical interaction between total serum cholesterol levels and statin use for the risk of haemorrhage (Interaction OR (IOR), 1.09; 95% CI 1.05 to 1.12). Increasing levels of total serum cholesterol were associated with a decreased risk of ICH within statin strata (average OR, 0.87; 95% CI 0.86 to 0.88 for every increase of 0.26 mmol/l of total serum cholesterol concentrations), while statin use was associated with an increased risk (OR, 1.54; 95% CI 1.31 to 1.81 of the average level of total serum cholesterol). The protective effect of serum cholesterol against ICH was reduced by statins in strictly lobar brain regions more than in non-lobar ones. Conclusions: Statin therapy and total serum cholesterol levels exhibit interaction effects towards the risk of ICH. The magnitude of such effects appears higher in lobar brain regions.